(untitled) (Contemporary Journal of Social Science Review, 2025)
Information-seeking behavior helps chronic patients obtain relevant health information, enabling better disease management and informed health decisions. This study investigates the influence of information-seeking behavior on informed decision-making. It also examines the effect of health information management and coping strategies in this relationship. This pilot study adopted a quantitative research design and included a sample of 100 participants selected from a population of chronic patients, were not part of the main study. A structured questionnaire was administered to patients with diabetes, hypertension, and chronic heart disease to collect data. Partial Least Squares-Structural Equation Modeling (PLS-SEM) v.4.1.1 was applied to test the proposed model by using descriptive analysis. The findings showed that information-seeking behavior is a significant predictor of informed decision-making. Moreover, health information management and coping strategies mediate this relationship in part, which underscores the significance of these two aspects in bringing information-seeking activities to successful decision-making. The research has practical implications for healthcare providers striving to enhance patient empowerment and self-management in chronic illness.